Obtención de un colorante a partir de los residuos producidos en la elaboración de la bebida a base de tusa de maíz negro (Zea mays L.) en la Parroquia de Guaytacama con la Asociación Virgen del Tránsito. - Marroquin Carua, Brandon David (2024)
This research project was set up with the purpose of making the most of and extracting the anthocyanins (natural pigment) of the waste (coronta) obtained from the elaboration of energy drinks based on black corn (Zea mays L.). The so called waste provides several benefits within the different agribusiness processes. Therefore, the main objective of this study is to obtain the dye from the black corn coronta (Zea Mays L.), throughout the extraction methodology using the rotavapor with four factors. The powder color of the mentioned product was obtained, due to spray drying with two factors. Also, the Design Expert program was carried out for the execution of statistical, experimental treatment and information processing. In addition, the numerical optimization model will be used through the surface design IV optimal for the experimental design. It will generate a mathematical equation that shows the tendency of the process conditions. The experimental design applied in this project, which purpose was the proposal for the optimization of the performance of anthocyanins and polyphenols threw up the following conditions: Temperature of 59.98 ° C, a time of 11.64, the mass/solvent ratio of 3 3 and with an ethanol concentration at 94.97%, addressing the best results in the realization of the run with a 41.45%anthocyanines yield, the polyphenol yield of 81.42%, apart from a desirability of 1. In the runs for the drying of the anthocyanins of the waste of black corn the best data obtained were: under conditions of air inlet of 170 ° C and a feed flow rate of 500 ml/h, aborting a performance of the performance of the 76.14%, an anthocyanin content of 4542.01 mg/1000g, a polyphenols content of 99.87 mg/1000g, a moisture percentage of 3.11 including a desirability of 0.971. The design that came up in this research project will serve as a basis for future studies about obtaining a natural dye, and thus an adequate decision can be made on the new sample with which it will be possible to improve the performance of anthocyanins and polyphenols in 75% with respect to previous thesis.